(untitled) (Eurasian Journal of History, Geography and Economics, 2025)
The importance of accounting balance information and ways oftheir effective use in quick analysis and assessment of the economic potential of economic entities are mentioned in the article. The issues of improving the method of express analysis through the quantitative calculation of production and financial potential, which are considered important components of the economic potential of the enterprise by external information users are covered